2010
DOI: 10.1007/s00464-010-1004-3
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic surgery for appendicectomy: a retrospective comparative analysis

Abstract: SILS appendicectomy seems to be a safe and efficacious technique. Further work in the form of randomized studies is required to investigate any significant advantages of this new and attractive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 21 publications
2
56
1
Order By: Relevance
“…By plotting the operation time against sequential case number (Figure 2), our data showed that the operation time decreased dramatically after approximately 13 cases were performed. This finding is consistent with previous observations by Chow et al, 4 who found that a relatively gradual learning curve of 10 to 13 surgeries was needed for an experienced surgeons to perform SILS. However, it is difficult to determine the specific learning curve for G-SILS appendectomy as every surgeon has a different laparoscopic skills set to start with.…”
Section: Discussionsupporting
confidence: 83%
“…By plotting the operation time against sequential case number (Figure 2), our data showed that the operation time decreased dramatically after approximately 13 cases were performed. This finding is consistent with previous observations by Chow et al, 4 who found that a relatively gradual learning curve of 10 to 13 surgeries was needed for an experienced surgeons to perform SILS. However, it is difficult to determine the specific learning curve for G-SILS appendectomy as every surgeon has a different laparoscopic skills set to start with.…”
Section: Discussionsupporting
confidence: 83%
“…4,[12][13][14][15][16][17][18] But the successive rate of SILS technique can be confirmed by prospective clinical trial but no study was found yet.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, in recent years, efforts to improve LA have led to a reduction in port size diameter and the number of laparoscopic access sites needed and to the introduction of SILS. [6][7][8][9] Between July 2008 and April 2013, 360 patients with colorectal cancer underwent laparoscopic surgery at our institution. Our experience with this surgical technique showed it to be safe and feasible, with good short-and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%